2008
DOI: 10.1007/s00420-008-0365-6
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and self-reported occupational injury in small and medium-sized companies

Abstract: Objectives This survey was designed to determine whether depressive symptoms had an eVect on the risk of self-reported occupational injury in South Korea. Methods We conducted a prospective follow-up survey of workers at 44 small-to medium-sized companies classiWed into manufacturing or service businesses; 1,350 questionnaires were used in the Wnal analysis. The Wrst survey requested information regarding personal characteristics, work characteristics, and depressive symptoms (CES-D); the second survey queried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…We were unable to identify occupational factors that were significantly associated with SPD in our study, including recent occupational injury and work area. This observation is discordant with findings from studies of other occupational populations that observe a significant association between occupational injury and poor mental health [1,3,11,20,21]. However, our findings are consistent with a recent study by Lander and colleagues of a similar workforce in the US [22].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We were unable to identify occupational factors that were significantly associated with SPD in our study, including recent occupational injury and work area. This observation is discordant with findings from studies of other occupational populations that observe a significant association between occupational injury and poor mental health [1,3,11,20,21]. However, our findings are consistent with a recent study by Lander and colleagues of a similar workforce in the US [22].…”
Section: Discussioncontrasting
confidence: 57%
“…A growing body of literature documents the association between occupational injury and poor mental health [1][2][3][4]. Although animal slaughter and meatpacking workers in the United States experience among the highest rates of occupational injury of all industries, there have been few studies of mental health in this workforce [5].…”
Section: Introductionmentioning
confidence: 99%
“…55 Several studies observed increased injury rates in employees reporting conflicts at work, either with coworkers or with supervisors, and a much higher incidence of self-reported injuries in those who had depressive symptoms. [56][57][58] Costs associated with these various workplace health/safety risks have also been well documented. A University of Michigan study showed that 85% of workers' compensation costs were attributed to worker health status tied to risk assessment.…”
Section: Making the Case For Integrating Workplace Health Protection mentioning
confidence: 99%
“…Research appears in fact to be mainly addressed to describing epidemiological associations, documenting hazards or risk factors, reporting data a posteriori, and the role of OH professionals seems to be underplayed (Burdorf et al 1997;Chau et al 2004Chau et al , 2007Chau et al , 2008Kim et al 2009;McLeod et al 2003;Palmer et al 2008;Porru et al 2006;Rivara and Thompson 2000). Also, few examples of intervention studies (IS) and effectiveness evaluation of prevention programmes are available in the literature either for specific OI or sectors (Lipscomb 2000;Mancini et al 2005;Miller et al 2007;Rautiainen et al 2008;van der Molen et al 2007).…”
Section: Introductionmentioning
confidence: 95%